Dampak Loyalitas dari Keputusan Konsumen Disebabkan Pelayanan dan Promosi pada Usaha Gimnastik - Aryanto, Rudy; Susanto, Susanto; Stefenny, Liu Santa (Bina Nusantara University, 2009)
This research purpose is to analyze the influence service quality and promotion to decision making and its impact on consumer loyalty. Method used in this research is descriptive-associative, using Pearson Correlation Path Analysis. Data gathered by distributiong questionnaire to 110 respondents in Gold’s Gym Thamrin City. From the data analysis, it is found out that the structural model is given as Y= 0,497X2 + 0,868, whereas R2 24,7% , and structural 2 Z = 0,491 X1 + 0,871 whereas R2=24,2. The service quality seems have less influence to consumer’s decision making but have stronger influence to consumer loyalty. Promotion effectively influences consumer’s decision making as much as 24,2%. Thus, service quality and promotion should be leveraged to increase sales and consumer loyalty.